2021
DOI: 10.15376/biores.16.4.8366-8378
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of cellulolytic enzymes and Lactobacillus bulgaricus on mycotoxins production and the quality of maize silage

Abstract: Fungal spoilage and mycotoxin contamination are two of the greatest hazards of silage. The present work was carried out to evaluate the impact of Lactobacillus bulgaricus and cellulolytic enzymes on the maize silage (MS) quality. Fungal analysis of different MS samples showed different mycotoxigenic fungi. The highest frequency (62.8%) was associated with Fusarium spp. Four species with different relative densities were found: F. graminearum (71.1%), F. culmorum (15.2%), F. proliferatum (11.2%), and F. oxyspor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Hence, the application of this fungus as microbial inoculants to plants would help to modify and degrade fumonisin thus preventing its invasion of crops. From the study of Bakri (2021) which evaluated the effect of T. harzianum and other cellulolytic enzymes on divers mycotoxin, it was found that this fungus together with Lactobacillus bulgaricus greatly inhibited the production of fumonisin and other mycotoxins.…”
Section: Role Of Microbial Inoculants In the Management And Control O...mentioning
confidence: 99%
“…Hence, the application of this fungus as microbial inoculants to plants would help to modify and degrade fumonisin thus preventing its invasion of crops. From the study of Bakri (2021) which evaluated the effect of T. harzianum and other cellulolytic enzymes on divers mycotoxin, it was found that this fungus together with Lactobacillus bulgaricus greatly inhibited the production of fumonisin and other mycotoxins.…”
Section: Role Of Microbial Inoculants In the Management And Control O...mentioning
confidence: 99%
“…The identification approaches documented the occurrence of three filamentous fungi on maize silage: Aspergillus flavus, A. niger, and Fusarium sp. Bakri (2021) demonstrated the presence of Aspergillus sp., Fusarium sp., Penicillium, Mucor sp., and Rhizopus sp. on maize silage.…”
Section: Fig 2 Hplc Chromatograph Of S Platensis Extractmentioning
confidence: 99%